2016
DOI: 10.1124/dmd.116.070722
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole Exacerbates Pemetrexed-Mediated Hematologic Toxicity by Competitive Inhibition of Renal Basolateral Human Organic Anion Transporter 3

Abstract: Pemetrexed, a multitargeted antifolate, is eliminated by tubular secretion via human organic anion transporter 3 (hOAT3). Although proton pump inhibitors (PPIs) are frequently used in cancer patients, the drug interaction between PPIs and pemetrexed remains to be clarified. In this study, we examined the drug interaction between pemetrexed and PPIs in hOAT3-expressing cultured cells, and retrospectively analyzed the impact of PPIs on the development of hematologic toxicity in 108 patients who received pemetrex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…Lansoprazole is known to be a potent inhibitor of hOAT3 [11, 15]. However, little is known about the stereoselective inhibitory potencies of lansoprazole against hOAT1 and hOAT3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lansoprazole is known to be a potent inhibitor of hOAT3 [11, 15]. However, little is known about the stereoselective inhibitory potencies of lansoprazole against hOAT1 and hOAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our recent study demonstrated that lansoprazole competitively inhibited hOAT3-mediated transport of pemetrexed, which has a structure and pharmacokinetics similar to those of methotrexate [15]. In addition, our retrospective clinical study demonstrated that co-administration of lansoprazole should increase the risk for the development of side effects (hematological toxicity) of pemetrexed [15]. These findings indicate that drug interaction between lansoprazole and hOAT3 substrates could be a cause of clinical problem.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations